A Case of Equitable Maritime Delimitation: Nicaragua and Colombia in the Western Caribbean Sea - Reichler, Paul S. (Revista Tribuna Internacional, 2013)
The unanimous judgment the International Court of Justice in November 2012 which resolved the boundary dispute between Nicaragua and Colombia in the western Caribbean Sea has generated considerable attention and commentary. Almost all of it has been highly favorable, with the sole exception of the reaction by Colombia, which purported to “reject” the Court’s Judgment and commenced procedures to withdraw its acceptance of ICJ jurisdiction in regard to future cases. This article demonstrates that the Court’s Judgment reflects the application of well-established legal principles of maritime boundary delimitation, and results in an equitable solution that is balanced and fair to both Parties. By analyzing the unique geographical circumstances of this case and discussing the methodologies and reasoning the Court employed in these circumstances to delimit the disputed maritime area, the article demonstrates that the delimitation line established by the Court was a creative solution to a difficult and complex geographic situation, which at the same time is firmly rooted in and consistent with well-established jurisprudence. As a result, the maritime boundary that the Court fixed between Nicaragua and Colombia allows the coasts of both States to generate maritime entitlements in a reasonable and mutually balanced way. Not only is the Court’s Judgment equitable to both Parties; it is also legally binding on them. There is no basis for either State to “reject” it, and no justification for refusing to entrust future cases to the Court, which remains an indispensable forum for the peaceful resolution of disputes between States according to the rule of law.